2020
DOI: 10.1192/bjo.2020.139
|View full text |Cite
|
Sign up to set email alerts
|

Public behaviour in response to the COVID-19 pandemic: understanding the role of group processes

Abstract: Background In the absence of a vaccine, behaviour by the public is key to the response to the COVID-19 pandemic. Yet, as with other types of crises and emergencies, there have been doubts about the extent to which the public are able to engage effectively with the required behaviour. These doubts are based on outdated models of group psychology. Aims and argument We analyse the role of group processes in the COVID-19 pandemic in three domains: recognition of threat, adherence by the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
2
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 47 publications
4
85
2
6
Order By: Relevance
“…Gonçalves et al (2021) also reported on the resilience and fast adaption to the changed realities of life in older adults. Some of the participants reported a newfound sense of shared community with neighbours and a feeling of national solidarity (see also Drury et al, 2021). In other words, in line with SIMIC, thriving was associated with maintaining, recovering and gaining new groups during this crisis, as these provide a range of psychological and social resources to cope more effectively with the social challenges of the situation .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Gonçalves et al (2021) also reported on the resilience and fast adaption to the changed realities of life in older adults. Some of the participants reported a newfound sense of shared community with neighbours and a feeling of national solidarity (see also Drury et al, 2021). In other words, in line with SIMIC, thriving was associated with maintaining, recovering and gaining new groups during this crisis, as these provide a range of psychological and social resources to cope more effectively with the social challenges of the situation .…”
Section: Discussionmentioning
confidence: 88%
“…Gonçalves et al (2021) discussed the repercussions of social isolation, pointing to the deprivations and negative affect experienced by older adults in different countries as the result of increasing social isolation during COVID-19. Conversely, works have also suggested some positive outcomes from the pandemic, in the form of increased community solidarity and support, which may counter the negative impacts of social isolation (Bowe et al, 2020;Drury et al, 2021;Jetten et al, 2020;Wolf et al, 2020). Previous research on crises demonstrates that people may experience increased belief in community efficacy (McNamara et al, 2013), and develop a new shared identity that can endure beyond the immediate disaster response time-period (Drury et al, 2016;Ntontis, et al, 2018).…”
Section: The Current Studymentioning
confidence: 99%
“…Both ONS (2020c) and the UCL survey (Fancourt et al, 2020c) reported in mid-July that only about half respondents were consistently maintaining physical distancing. In terms of process or mechanism, these trends are contemporaneous with several factors, all of which could contribute (Drury, Carter, Ntontis, & Tekin Guven, 2021): decline in trust in the government (Fancourt et al, 2020c, p. 16), decline sense of national togetherness , and decline in perceived risk (ONS, 2020b). Over the summer and early autumn, however, adherence levels, including distancing, levelled off and remained relatively high, with little evidence of public 'fatigue' (Michie, West, & Harvey, 2020)…”
Section: Trends In Distancing Behaviours and Relevant Beliefs/ Perceptions That Occurred With The Easing Of 'Lockdown'mentioning
confidence: 99%
“…Longitundinal survey studies (Hagger et al, 2020;Hamilton et al, 2020;Norman et al, 2020;Rozendaal et al, 2020;Van Bavel et al, 2020;Vignoles et al, 2021) and guidance documents / recommendation papers (e.g. Bonell et al, 2020;Drury et al, 2021;SPI-B, 2020;Templeton et al, 2020) have identified several predictors that are associated with the theoretical domains of social influences, beliefs about capability, beliefs about consequences, behavioural regulation, and knowledge. These predictors influenced subsequent physical distancing behaviour.…”
Section: Systematic Review Of Interventions To Promote Physical Distancing Behaviours During Pandemics/epidemics Of Infectious Diseases Smentioning
confidence: 99%